Pilot Scale Study on the Prevalence and Associated Risk Factors of Canine Distemper and Canine Parvovirus in Ahmadabad and Gandhinagar Cities of Gujarat, India - Amit Kumar Singh; Mukta Jain; Kalgi Joshi; Shilangi gupta; Amit Kumar Verma; Amit Kumar; Saurabh Gupta; Jagdip Singh Sohal (The Indian Veterinary Journal, 2024)
Canine parvovirus (CPV) and canine distemper virus (CDV) infections are the most common and contagious viral infections of dogs.  The present study investigated the burden of CPV and CDV infections among the domestic dogs in Ahmadabad and Gandhinagar cities of Gujarat, India with the specific objective of determining the case prevalence and the associated risk factors of the disease. Faceal samples were collected from dogs (n = 507) attended at different private and government veterinary polyclinics, from 2020 to 2021. Data regarding sex, age and season were recorded with respect to prevalence case Faecal samples were tested for CPV using Ubio Quick VET Canine Parvovirus antigen rapid test kit and (nasal and ocular secretion)were tested for CDV antigen using canine distemper virus antigen rapid test kit. The results of the present study revealed an overall case prevalence of 8.68% for both infections, while 5.71% and 11.63% Case prevalence were reported for CPV and CDV, respectively. The Case prevalence among dogs examined according to sex was 6.82% for CPV and 11.36% for CDV in male and 3.23% for CPV and 12.26% for CDV in female. Pups had the higher Case prevalence of both infections than those of adults. Case prevalence of DV infection was high in the winter season (14.40%), while the lowest (3.03%) in monsoon season. For CPV also Case prevalence (7.67%)was higher in winter season while no prevalence reported for CPV in summer. Age, sex and seasonal variations may be considered as possible risk factors in the Case prevalence of CPV and CDV infections. Thus, the identification of the potential risk factors associated with these diseases may be helpful for designing their prevention and control strategies.